PERAMALAN PASOKAN BAHAN BAKU DAN PENJUALAN SIR 20 DI PT. PERKEBUNAN NUSANTARA VII UNIT PADANG PELAWI KEC. SUKARAJA KAB. SELUMA - Manihuruk, Eka Monika; Romdhon, M. Mustopa; Nusril, Nusril (Jurnal AGRISEP, 2016)
This research aims to forecast supply of raw material and sales and then to analyze the price of SIR 20 for 1 next year with a best method. Accuracy method of divination used MAD, MSE, MAPE. Analyze quantitative used time series, eksponential smoothing and Arima the development of raw materials, price of raw materials inside and outide of companies, the price of SIR 20 and selling of SIR 20 through increasing.